Genomic features of renal cell carcinoma with venous tumor thrombus - Warsow, Gregor; Hübschmann, Daniel; Kleinheinz, Kortine; Nientiedt, Cathleen; Heller, Martina; Van Coile, Laura; Tolstov, Yanis; Trennheuser, Lukas; Wieczorek, Kathrin; Pecqueux, Carine; Gasch, Claudia; Kuru, Timur Hasan; et al. (Scientific reports, 2018)
A venous tumor thrombus (VTT) is a potentially lethal complication of renal cell carcinoma (RCC) but virtually nothing is known about the underlying natural history. Based on our observation that venous thrombi contain significant numbers of viable tumor cells, we applied multiregion whole exome sequencing to a total of 37 primary tumor and VTT samples including normal tissue specimens from five consecutive patients. Our findings demonstrate mutational heterogeneity between primary tumor and VTT with 106 of 483 genes (22%) harboring functional SNVs and/or indels altered in either primary tumor or thrombus. Reconstruction of the clonal phylogeny showed clustering of tumor samples and VTT samples, respectively, in the majority of tumors. However, no new subclones were detected suggesting that pre-existing subclones of the primary tumor drive VTT formation. Importantly, we found several lines of evidence for "BRCAness" in a subset of tumors. These included mutations in genes that confer "BRCAness", a mutational signature and an increase of small indels. Re-analysis of SNV calls from the TCGA KIRC-US cohort confirmed a high frequency of the "BRCAness" mutational signature AC3 in clear cell RCC. Our findings warrant further pre-clinical experiments and may lead to novel personalized therapies for RCC patients.
Gesehen am 26.06.2019